2009
DOI: 10.1016/j.geoderma.2008.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of north and south exposure on organic matter in high Alpine soils

Abstract: The present work focuses on the subalpine range of the Italian Alps to determine the influence of aspect and consequently climate on soil humus properties and chemistry. This was done by comparing soils developing in north-and south-facing sites on siliceous parent material. The soils were investigated with respect to the total organic C and N content, C and N contents of organic matter (OM) density fractions and of labile(oxidised by H2O2) and stable (H2O2-resistant) fractions. Further characterisation of OM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
51
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 57 publications
13
51
0
2
Order By: Relevance
“…In line with previous studies performed in the Trentino area (Egli et al 2006(Egli et al , 2009Fravolini et al 2016;Bardelli et al 2017), the soils located at the north-facing slope were moister and richer in total C and nitrogen contents compared to those at the south-facing slope. Along a climosequence, Fravolini et al (2016) observed faster decay rates of the P. abies wood blocks at the north-than at the south-facing slopes up to an elevation of 1,800 m a.s.l., probably because of the higher soil moisture and clay content along with a lower soil pH.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with previous studies performed in the Trentino area (Egli et al 2006(Egli et al , 2009Fravolini et al 2016;Bardelli et al 2017), the soils located at the north-facing slope were moister and richer in total C and nitrogen contents compared to those at the south-facing slope. Along a climosequence, Fravolini et al (2016) observed faster decay rates of the P. abies wood blocks at the north-than at the south-facing slopes up to an elevation of 1,800 m a.s.l., probably because of the higher soil moisture and clay content along with a lower soil pH.…”
Section: Discussionsupporting
confidence: 91%
“…Mountain Alpine ecosystems have gained increasing attention during the past several years because they are particularly sensitive to ever-changing climatic conditions (Egli et al 2006(Egli et al , 2009. Indeed, an increase of about 2°C has been recorded in the annual minimum temperature in the European Alps during the twentieth century (Beniston, Diaz, and Bradley 1997).…”
Section: Introductionmentioning
confidence: 99%
“…2A) (Hedenström and Possnert, 2001;Doner, 2003). Such an old carbon effect might originate from the input of stable and old refractory organic matter present in Alpine podzols Egli et al, 2009). A relatively old 14 C date of macrorests was found for the beginning of the record (ca 14315 BC at 119 cm), confirming the age of the earliest formation of Pleistocene/Holocene -age Alpine soils (Favilli et al, 2008).…”
Section: Meidsee Age Modelmentioning
confidence: 69%
“…On the other hand, elevation and temperature differences are identified as the dominant controls on mountain SOC at regional scales (Djukic et al 2010;Van Miegroet et al 2007, 2005; Leifeld et al 2005), local topographic changes (e.g., slope curvature and aspect, Egli et al 2009;Tan et al 2004), soil properties (e.g., soil type, soil moisture, pH and clay-content; Djukic et al 2010;Leifeld et al 2005), and vegetation (e.g., type and stand age; Luyssaert et al 2008;Zhou et al 2006) may introduce a large variability of mountain SOC at local scales. Small-scale variability may even impose strong scatter at large-scales and conceal relationships between SOC, topography, and climate.…”
Section: Introductionmentioning
confidence: 99%